2015
DOI: 10.2147/cia.s73396
|View full text |Cite
|
Sign up to set email alerts
|

Associations between apolipoprotein E gene polymorphisms and Alzheimer’s disease risk in a large Chinese Han population

Abstract: ObjectiveApolipoprotein E gene (APOE) polymorphisms contributing to the risk of sporadic Alzheimer’s disease (AD) have been identified for decades, but it has not been investigated in large AD samples of Chinese Han population.MethodsWe performed a cross-sectional study to explore the effect of APOE polymorphisms on sporadic AD in 875 sporadic AD patients and 1,195 cognitive normal controls of Chinese Han. Genotyping of APOE was determined by multiplex amplification refractory mutation system polymerase chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…We observed a stronger effect of the variant in APOE (rs429358) on Aβ positivity in the Korean population than that in the European population (Korean, OR = 5.275; European, OR = 1.197 [11]). This is similar to the results in previous studies of the East Asian population, in which the effect of APOE ɛ4 on AD risk was stronger in Han Chinese [48] and Japanese [47] than in the European population. Furthermore, outside the APOE locus, previously reported Aβ associated SNPs in European ancestry data were not replicated [11] in our cohort.…”
Section: Discussionsupporting
confidence: 91%
“…We observed a stronger effect of the variant in APOE (rs429358) on Aβ positivity in the Korean population than that in the European population (Korean, OR = 5.275; European, OR = 1.197 [11]). This is similar to the results in previous studies of the East Asian population, in which the effect of APOE ɛ4 on AD risk was stronger in Han Chinese [48] and Japanese [47] than in the European population. Furthermore, outside the APOE locus, previously reported Aβ associated SNPs in European ancestry data were not replicated [11] in our cohort.…”
Section: Discussionsupporting
confidence: 91%
“…Although the APOE ε4 allele is one of the most well-established AD risk factors and the genetic variant that by far confers the strongest effect on disease risk [6,10,49], most studies of this association in non-EuroA populations have not precisely quantified for APOE genotype-associated risks for ε4 heterozygotes and ε4 homozygotes with notable exceptions of AAs [10,27], Caribbean Hispanics [50], Indians [51], and Han Chinese [52]. Similar to Chinese [52], our study showed that the effect of ε4 on AD risk was stronger in Koreans and Japanese than in EuroAs and other non-EuroA populations, including AAs, Indians, and Israeli-Arabs [53]. Ethnic differences in the effect size of this association might be due to differences in allele frequency such that the proportional difference in the ε4 frequency between cases and controls resulted in a larger odds ratio even though the absolute difference in the allele frequency was similar across the population.…”
Section: Discussionmentioning
confidence: 99%
“…Its encoding protein, Apolipoprotein E, consists of 299 amino acids and is a cholesterol carrier involving in lipid transportation and injury repair in the brain. APOE ε4 increased the risk of AD in a dose-dependent manner, in contrast to APOE ε 2, which plays a protective role ( Bertram et al , 2007 ; Sando et al , 2008 ; Bonner-Jackson et al , 2012 ; Wu et al , 2015 ).…”
Section: Introductionmentioning
confidence: 85%